Re-Engaging Cross-Reactive Memory B Cells: The Influenza Puzzle - Ellebedy, Ali H.; Ahmed, Rafi (Frontiers in Immunology, 2012)
The emergence of a novel influenza A virus strain into humans poses a continuous public health threat. Vaccination is the most effective means of protection against influenza. The generation of memory B cells and long-lived plasma cells (PCs) that can maintain protective levels of influenza-specific antibodies for protracted periods of time is the foundation for the success of such vaccines. Influenza vaccines elicit an antibody response that is primarily targeting viral surface glycoproteins. However, frequent amino acid mutations within the immunodominant epitopes allow the virus to efficiently escape neutralization by pre-existing antibodies and consequently cause annual epidemics and occasional pandemics. Recently, monoclonal antibodies (mAbs) that target subdominant influenza epitopes have been extensively characterized. These epitopes are immunogenic, can mediate virus neutralization, and most importantly are conserved among different influenza strains. It remains puzzling, however, that despite being repeatedly exposed to such conserved domains of influenza HA either in the form of vaccination or natural infection, most humans do not develop immunological memory that can provide broad protection against emerging virus strains. Here we will discuss the conditions that may be required for engaging such cross-reactive memory B cells in the immune response to influenza infection and vaccination in humans.